High fat feeding affects the number of GPR120 cells and enteroendocrine cells in the mouse stomach - Widmayer, Patricia; Goldschmid, Hannah; Henkel, Helena; Küper, Markus; Königsrainer, Alfred; Breer, Heinz (Frontiers in Physiology, 2015)
Long-term intake of dietary fat is supposed to be associated with adaptive reactions of the organism and it is assumptive that this is particularly true for fat responsive epithelial cells in the mucosa of the gastrointestinal tract. Recent studies suggest that epithelial cells expressing the receptor for medium and long chain fatty acids, GPR120 (FFAR4), may operate as fat sensors. Changes in expression level and/or cell density are supposed to be accompanied with a consumption of high fat (HF) diet. To assess whether feeding a HF diet might impact on the expression of fatty acid receptors or the number of lipid sensing cells as well as enteroendocrine cell populations, gastric tissue samples of non-obese and obese mice were compared using a real time PCR and immunohistochemical approach. In this study, we have identified GPR120 cells in the corpus region of the mouse stomach which appeared to be brush cells. Monitoring the effect of HF diet on the expression of GPR120 revealed that after 3 weeks and 6 months the level of mRNA for GPR120 in the tissue was significantly increased which coincided with and probably reflected a significant increase in the number of GPR120 positive cells in the corpus region; in contrast, within the antrum region, the number of GPR120 cells decreased. Furthermore, dietary fat intake also led to changes in the number of enteroendocrine cells producing either ghrelin or gastrin. After 3 weeks and even more pronounced after 6 months the number of ghrelin cells and gastrin cells was significantly increased. These results imply that a HF diet leads to significant changes in the cellular repertoire of the stomach mucosa. Whether these changes are a consequence of the direct exposure to high fat in the luminal content or a physiological response to the high level of fat in the body remains elusive.